2014
DOI: 10.18632/oncotarget.2742
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K inhibitor GDC-0941 displays promisingin vitro and in vivoefficacy for targeted medulloblastoma therapy

Abstract: Deregulation of the Phosphoinositide 3-kinase (PI3K)/AKT signalling network is a hallmark of oncogenesis. Also medulloblastoma, the most common malignant brain tumor in children, is characterized by high levels of AKT phosphorylation and activated PI3K signalling in medulloblastoma is associated with enhanced cellular motility, survival and chemoresistency underscoring its role of as a potential therapeutic target. Here we demonstrate that GDC-0941, a highly specific PI3K inhibitor with good clinical tolerabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…Our studies and those of others have shown that Myc can confer metastatic phenotypes in medulloblastoma (6)(7)(8). Although mechanisms of Myc-mediated transformation in medulloblastoma remain largely unknown, multiple lines of data suggest Mycdriven medulloblastoma are dependent on PI3K/AKT signaling (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and point to the PI3K/AKT axis as a critical downstream effector of Myc in group 3 medulloblastoma (7,16,17). Activation of PI3K/AKT signaling has been shown to promote various oncogenic phenotypes in medulloblastoma including enhanced tumor growth, metastasis, and chemoresistance (14,(18)(19)(20)(21)(22).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our studies and those of others have shown that Myc can confer metastatic phenotypes in medulloblastoma (6)(7)(8). Although mechanisms of Myc-mediated transformation in medulloblastoma remain largely unknown, multiple lines of data suggest Mycdriven medulloblastoma are dependent on PI3K/AKT signaling (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and point to the PI3K/AKT axis as a critical downstream effector of Myc in group 3 medulloblastoma (7,16,17). Activation of PI3K/AKT signaling has been shown to promote various oncogenic phenotypes in medulloblastoma including enhanced tumor growth, metastasis, and chemoresistance (14,(18)(19)(20)(21)(22).…”
Section: Introductionsupporting
confidence: 52%
“…To date, multiple studies have demonstrated that pharmacologic inhibitors of PI3K signaling have potent antineoplastic effects in medulloblastoma (7,13,14,16,17,19,36), and underscore the importance of PI3K signaling particularly in Myc-driven medulloblastoma. To effectively exploit PI3K/AKT signaling for medulloblastoma treatment, it would be important to delineate the extent of the Myc-PI3K/AKT signaling axis through identification of novel targetable effector and mediators of this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[84] The highly specific pan-PI3K inhibitor GDC-0941 has recently been shown to have anti-migratory, anti-proliferative and proapoptotic effects in MB cell lines, showing synergy with the standard chemotherapeutic drug etoposide and good clinical tolerability. [85] Other elements of the PI3K/AKT pathway are also being considered as potential targets to inhibit cell proliferation and migration in GBM and MB. One example is AKT, which usually shows high levels of phosphorylation in these brain tumors.…”
Section: Emt Cell Invasion and Motilitymentioning
confidence: 99%
“…Therefore, inhibiting this signaling pathway may facilitate chemotherapy treatments (7,8). Preclinical studies and early clinical trials indicate that the treatment of several cancers including breast (9), lung (10), medulloblastoma (11), and pancreatic cancer (6) could benefit from PI3K inhibitors. It is plausible that such targeted therapeutic approaches against the PI3K/AKT pathway can be used in patients with advanced bladder cancer, either as a single agent or in combination, to decrease drug resistance and augment the efficacy of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%